IMPLEMENTASI IRIGASI TETES (DRIP IRRIGATION) PADA BUDIDAYA SEMANGKA DI LAHAN KERING DESA REMPEK KABUPATEN LOMBOK UTARA - Wardhana, Agung Widya; Baharuddin; Siti Zainab; Zainal Arifin; Mirfatul Hidayah; Baiq Azizah Haryantini; Wawan Apzani; I Made Sunantra (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Rempek Village has a potential of 760.18 hectares of dry land, or 31.80% of the total area, which has not been optimally utilized. The availability of 4 units of groundwater pump machines built since 1990 has not been utilized by the community because the groundwater pump well outlets are not equipped with irrigation channels. The community only utilizes dry land during the rainy season, with the main crops being rice, corn, cassava, and several types of secondary crops. To inspire the community to utilize groundwater pump wells in Rempek Village, the Faculty of Agriculture Team from Universitas 45 Mataram conducted a community service activity on the implementation of drip irrigation technology in the cultivation of watermelon plants on dry land in Rempek Village. The results of this community service activity are: a) farmers were given an understanding of the optimization of dry land by utilizing existing water resource potential; b) farmers practiced the installation and operation of drip irrigation networks, and c) farmers were given knowledge and practical experience in watermelon cultivation. The results of the application of drip irrigation technology provided understanding on: a) increasing the planting period on dry land, allowing farmers to grow more crops and increase their income; b) ensuring a stable water supply for crop cultivation, which can increase agricultural productivity and reduce the risk of crop failure; c) the potential for increased income through crop cultivation during the dry season, thus improving farmers' income and welfare; and d) increased use of groundwater resources, which is beneficial for improving agricultural productivity.